High‐thermal conductivities of epoxy composites via p‐phenylenediamine interfacial modification and process intensification. Issue 41 (2nd June 2021) - Bao, Di; Xu, Fei; Cui, Yexiang; Yuan, Sicheng; Zhang, Xiguang; Zhu, Yanji; Gao, Yueyang; Wang, Huaiyuan
Abstract: High loadings of fillers are usually needed to achieve high‐thermal conductivity (TC) of polymer‐based composites, which inevitably sacrifices processability and meanwhile causes high‐cost. Therefore, it is of great significance to achieve high‐TC composites under low‐filler loading. Here, a novel p‐phenylenediamine (PPD) modified expanded graphite (EG‐PPD)/epoxy (EP) composite with high TC and low‐filler content was successfully prepared via pre‐dispersion and vacuum assisted mixing strategy. With the improved interfacial compatibility between EG and EP by PPD, the prepared EG‐PPD/EP composite exhibited excellent thermal management performance, resulting in the TC of which reached 4.00 W·m −1 ·K −1 with only 10 wt% (5.59 vol%) of EG‐PPD, which is approximately 19 times higher than that of pure EP. Meantime, the interface thermal resistance of EG‐PPD/EP composite between EG‐PPD and EP is reduced by 33% compared with EG/EP composite. This composite with excellent TC property is expected to be used in thermal management field. Abstract :